Significance of Cigarette Smoking among Youth with Bipolar Disorder - Goldstein, Benjamin I. (2008)
Cigarette smoking among adults with bipolar disorder (BP) correlates with psychosis, substance use disorders (SUD), and suicidality. Little is known regarding smoking among youth with BP. Youth with BP (N=441) were divided into three smoking groups: Never, Ever, and Daily. Twenty-five percent reported any smoking (11% Daily, 14% Ever). Ever and Daily subjects had significantly greater lifetime prevalence of suicide attempts, physical abuse, conduct disorder, and SUD, versus Never subjects. Daily heavy smokers had greater prevalence of SUD and suicide attempts, and worse depression versus Daily light smokers. Smoking among youth with BP is independently associated with suicide attempts and SUD.